(untitled) (International Journal of Engineering and Computer Science, 2018)
One of the key security threats on the Internet are called Compromised machines. The compromised machines in the network are recognize or distinguish using SPOT algorithm. SPOT algorithm is worked on The basis of powerful statistical tool called as Sequential Probability Ratio Test (SPRT) [1]. The Proposed system Spam Zombie Detection and Blocking Mechanism is an online spam zombie detection system in network which designed with Iterative Dichotomiser 3 (ID3) type logic which will increase the existing system performance and efficiency along with the detection it will also blocks the zombie system detected within the network. Proposed system is designed for the private mailing system. It also try to provide the enhanced security mechanism by blocking hacked machines.